The role of microRNAs in colorectal liver metastasis: Important participants and potential clinical significances - Dongxu Wang; Jie Liu; Tingting Huo; Yaowen Tian; Lei Zhao (Tumor Biology)
Colorectal cancer is one of the most common cancers in the world, and liver metastasis is the leading direct cause of cancer-related deaths in colorectal cancer. MicroRNA is involved in tumor metastasis in many aspects; mounting studies have shown that microRNAs play important roles in colorectal liver metastasis. Although lots of reviews about the association between microRNAs and colorectal cancer metastasis have been published, the reviews specifically focusing on microRNAs and colorectal liver metastasis are still lacking in the literature. To address this issue, here, we summarize the underlying mechanisms of microRNAs in colorectal liver metastasis and explore their potential clinical applications in this aspect.